Caracterização do ciclo sono/vigília de professores do ensino médio em natal/rn - Souza, Jane Carla de (2010)
In the school environment is fundamental the knowledge about the sleep-wake cycle (SWC), because we find children and adolescents with excessive sleepiness and learning difficulties. Furthermore, teachers with high demand and with different work schedule, which may contribute to changes in SWC. The aim of this study was to describe the SWC of high school teachers in Natal/RN. Habits and knowledge about sleep, chronotype, SWC, daytime sleepiness, sleep quality and job satisfaction were described in 98 high school teachers from public and private school. These parameters were compared according to the characteristics of work, family structure and gender. Data collection was performed with the use of questionnaires in two stages: 1) "health and sleep" (general characterization of sleep habits), Horne & Ostberg questionnaire (characterization of chronotype), Epworth Sleepiness Scale and the Index of Pittsburg Sleep Quality, 2) The sleep diary for 14 days. From the results, we observe that the teachers woke up and went to bed earlier in the week and showed a reduction of time in bed around 42min comparing to weekend. This reduction in time in bed during the week was accompanied by an increase in nap duration on weekend. In addition the teachers woke up earlier on Saturdays than on Sundays, probably due to housework and leisure. The teachers' knowledge about sleep was low in relation to individual differences and effect of alcoholic beverages on sleep, and high in the consequences of sleep deprivation. The differences found in comparisons on the characteristics of work, family structure and gender were punctual, except concerning the work schedule. The teacher who started work in the morning and finished in the night, woke up earlier, went to bed later and had less time in bed, when compared to teachers who work only in two shifts. In addition, teachers with late chronotypes who begin the work in the morning had a greater irregularity in the wake up time compared to teachers with earlier and intermediate chronotypes. Half of teachers have excessive sleepiness, which was positive correlated with work dissatisfaction. In general, teachers showed IPSQ averages equivalent to poor sleep quality and the women showed worst averages. From the results, it is suggested that the SWC of teachers varies according to work schedule, leading to irregularity and partial sleep deprivation in the week, although these responses vary according to chronotype. These changes are accompanied by excessive daytime sleepiness and poor sleep quality. However, it is necessary to expand the sample to clarify the influence of variables related to work, family structure and gender together